Broadening the phenotype of LRP2 mutations: a new mutation in LRP2 causes a predominantly ocular phenotype suggestive of Stickler syndrome. (23rd September 2013) - Schrauwen, I.; Sommen, M.; Claes, C.; Pinner, J.; Flaherty, M.; Collins, F.; Van Camp, G.
<x xml:space="preserve">Abstract</x> Two siblings, from a consanguineous Iraqi family, were investigated to identify the underlying genetic cause of their high myopia, esotropia, vitreous changes and cataract. Subsequent investigation identified low molecular weight proteinuria as part of their syndrome. Exome sequencing of one of the probands revealed a new non‐synonymous variant in the LRP2 gene. Sanger sequencing confirmed the mutation and segregation in the family. No mutation was identified in COL9A1/2, COL11A1/2, or COL2A1 genes. The variant (c.11483A>G; p.Asp3828Gly) is predicted to be damaging and is conserved among vertebrate species. Mutations in LRP2 have been shown to cause the Donnai–Barrow syndrome (DBS) or facio‐oculo‐acoustico‐renal (FOAR) syndrome, a syndrome associated with facial dysmorphism, ocular anomalies, sensorineural hearing loss, low molecular weight proteinuria, and diaphragmatic hernia and absent corpus callosum, although there is variability in the expression of some features. This family shows a milder phenotype with a predominant eye phenotype similar to the Stickler syndrome and only a few features of the DBS, including microglobulinuria. The presence of microglobulinuria was only detected after molecular results were known. In conclusion, with the identification of a new mutation in LRP2 associated with a predominant eye phenotype similar to the Stickler syndrome, we have broadened the phenotypic spectrum of LRP2 mutations.